Arguments for the optimisation of using biomass for energy production - Takács, István; Takács-György , Katalin (Applied Studies in Agribusiness and Commerce, 2013)
Using biomass to produce energy is not a new idea. In the past, the by-products of energy(?) production processes or naturally grown materials were mainly used for energy production. At the same time, during the production of biomass the conventional sources of energy are used (fuels, the embodied energy of which is used in the production of the biomass and equipment, etc.) which must be taken into account when determining the net energy production. This research aims to examine how to optimise the production and use of biomass energy and its supply chain in the energetic and economic criteria system, as well as how to impact upon the managing models of the processes to the energetic and economic parameters of the supply chain; we ask what criteria characterise the natural (environmental), economic and social sustainability, and how they can be implemented e.g. within the framework of an innovation cluster. This article describes a test model, and analyses the results of the model examinations and the conditions for compliance with sustainability criteria. Arguing the environmental, economic and social sustainability among the criteria of the model for evaluation is not possible at all times by means of direct indicators. The results of the research proved that only multi-criteria optimisation models serve a proper decision-making instrument for the evaluation of biomass utilisation for energy production.